Ultimate guide to trail running : everything you need to know about equipment, finding trails, nutrition, hill strategy, racing, avoiding injury, training, weather, and safety /: everything you need to know about equipment, finding trails, nutrition, hill strategy, racing, avoiding injury, training, weather, and safety. (2023) - Chase, Adam W; Hobbs, Nancy, 1960-
No abstract available